THE FACTORS INFLUENCING STUDENTS' SATISFACTION WITH BLENDED TEACHING METHODS IN THE CONTEXT OF INTERNATIONALIZATION OF EDUCATION AT FOREIGN TRADE UNIVERSITY - Thanh, Trịnh Ngọc (International Journal of Application on Economics and Business, 2024)
This study is to determine the factors affecting the students' satisfaction with the blended teaching method, especially in the current international context, making some recommendations to increase the students' satisfaction with the combined teaching method. The research sample is 200 students of Foreign Trade University, using EFA factor analysis to create 4 factors affecting the level of student satisfaction with the teaching method in teaching methods, content of instruction, characteristics of blended learning systems, infrastructure and technology. The research results contribute to help university leaders to consider improving teaching quality and applying information technology to innovate teaching methods in general and English teaching method in particular.